Safety assessment and remedial measures design for an extensive rockfall along the main road to Kimi, East Euboea, Greece - Loupasakis, C.; Lalos, G.; Rozos, D. (Bulletin of the Geological Society of Greece, 2013)
The steep morphology and the intense tectonic fragmentation of the mountainous areas of Greece combined with the dense road network create conditions favorable for the manifestation of rockfalls. Numerous events are recorded through the years, some of them causing injuries or even worse loss of lifes. The rockfall that took place along the Kimi – Platana – Paralia provincial road on August 2008, was studied in detail and is presented in the current paper. The rock detachment area was defined 200m away and at an altitude of 140m (130m higher from the road), while the rock pieces detached had a maximum volume of 4m3. The final consequences were two crashed cars and a heavily injured civilian. The causual factors as well as the proposed remedial measures, estimated by the use of RocFall by Rockscience Ltd., are described in detail. Furthermore, the temporary remedial measures applied by contractors are evaluated, pointing their defects.